Sexual Behaviour and Czech Culture - Schindler, Franz (Lidé města, 2001)
Starting point for this papet are the surprising results of a representative study of the sexual behaviour of the Czech people. In comparison to other people Czechs proved to 1. have more often and longer sex aod 2. are more likely to engage in extramarital relations and feel that such behaviour is normal. This paper discusses such socio-historical backgrounds as atheism and the socialist economical system and argues that since the 60_s Czech culture (especially in literature and film) has influenced the sexual behaviour by emphasizlng creative sex scenes and by uncritically depicting extramarital relations as a very common behaviour. The two Oscar-winning movies „Ostře sledované vlaky" (1966) and „Kolja" (1996) are analysed in support of this hypothesis.